2018
DOI: 10.1186/s12917-018-1694-7
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming species barriers: an outbreak of Lagovirus europaeus GI.2/RHDV2 in an isolated population of mountain hares (Lepus timidus)

Abstract: BackgroundPrior to 2010, the lagoviruses that cause rabbit hemorrhagic disease (RHD) in European rabbits (Oryctolagus cuniculus) and European brown hare syndrome (EBHS) in hares (Lepus spp.) were generally genus-specific. However, in 2010, rabbit hemorrhagic disease virus 2 (RHDV2), also known as Lagovirus europaeus GI.2, emerged and had the distinguishing ability to cause disease in both rabbits and certain hare species. The mountain hare (Lepus timidus) is native to Sweden and is susceptible to European brow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
68
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 32 publications
8
68
0
Order By: Relevance
“…Leeks and colleagues established a link between co-infection and viral diversity, as more diverse populations can produce more virulent infections and better adapt to new hosts 60 . This might explain the array of hare species infected by GI.2 [13][14][15][16][17] , which constitutes a novelty in relation to GI.1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leeks and colleagues established a link between co-infection and viral diversity, as more diverse populations can produce more virulent infections and better adapt to new hosts 60 . This might explain the array of hare species infected by GI.2 [13][14][15][16][17] , which constitutes a novelty in relation to GI.1.…”
Section: Discussionmentioning
confidence: 99%
“…GI.2 was identified as a novel pathogenic form of lagovirus in France in 2010 8 . Field observations and further characterisation of the strains revealed unique characteristics in comparison with former strains such as the ability to cross the species boundaries [13][14][15][16][17] and to kill young rabbits 11,12 . Previous studies also revealed the occurrence of recombination of GI.2 strains with non-pathogenic (GI.4) and pathogenic (GI.1a and GI.1b) strains [24][25][26] , showing an important role of recombination in generating diversity in GI.2 and confirming the high capacity of recombination within lagoviruses.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, RHDV2 can cause infection not only in young rabbits, including those aged 11 days (Dalton et al, 2012), which used to be considered resistant to the old RHDV genotypes; but also in vaccinated rabbits (Le Gall-Recule et al, 2013), which has also been confirmed in Poland (Fitzner & Niedbalski, 2018). It was also evidenced that RHDV2 causes diseases in other lagomorph species, including the Sardinian Cape hare (Lepus capensis mediterraneus) (Puggioni et al, 2013), Corsican (Italian) hare (Lepus corsicanus) (Camarda et al, 2014), Iberian hare (Lepus granatensis) (Lopes et al, 2014) and European hare (Lepus europaeus) (Hall et al, 2017), and recently even in the mountain hare (Lepus timidus) (Neimanis et al, 2018) and hares in England (Bell et al, 2019), unlike RHDV and RHDVa, which are believed to be characteristic for the European rabbit (Oryctolagus cuniculus). The latest case of infection is the sixth Lepus species to be infected with RHDV2, which suggests that the susceptibility to RHDV2 can be widespread among the Lepus species (Neimanis et al, 2018;Bell et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It was also evidenced that RHDV2 causes diseases in other lagomorph species, including the Sardinian Cape hare (Lepus capensis mediterraneus) (Puggioni et al, 2013), Corsican (Italian) hare (Lepus corsicanus) (Camarda et al, 2014), Iberian hare (Lepus granatensis) (Lopes et al, 2014) and European hare (Lepus europaeus) (Hall et al, 2017), and recently even in the mountain hare (Lepus timidus) (Neimanis et al, 2018) and hares in England (Bell et al, 2019), unlike RHDV and RHDVa, which are believed to be characteristic for the European rabbit (Oryctolagus cuniculus). The latest case of infection is the sixth Lepus species to be infected with RHDV2, which suggests that the susceptibility to RHDV2 can be widespread among the Lepus species (Neimanis et al, 2018;Bell et al, 2019). Holms and Grenfell (Holms & Grenfell, 2009) explain that the occurrence of new variants of the virus in the wild is the result of four factors: (1) adaptive evolution of the host's genes that engage in the most thorough interaction with the host's immune response, and react at the "host-pathogen" level, (2) interaction among the locally circulating viruses, (3) possible outbreak dynamics in time and space, and (4) disease spread control methods.…”
Section: Introductionmentioning
confidence: 99%
“…RHDV2 is a new lagovirus that was first reported in Europe in 2010 (Dalton et al, ; Le Gall‐Recule et al, ). It is not only genetically distinct from RHDV and RHDVa but, unlike RHDV and RHDVa, is also able to cause highly fatal disease in very young rabbits (Dalton, Nicieza, Abrantes, Esteves, & Parra, ; Neimanis, Pettersson, Huang, Gavier‐Widen, & Strive, ) and is capable of fatally infecting several species of hares (Camarda et al, ; Hall et al, ; Le Gall‐Recule et al, ; Neimanis, Ahola, et al, ; Puggioni et al, ; Velarde et al, ). Since its arrival in Australia, RHDV2 has become the dominant strain circulating in the field, seemingly replacing older RHDV strains and accounting for the majority of reported cases in wild and domestic rabbits (Mahar, Hall, et al, ).…”
Section: Introductionmentioning
confidence: 99%